Evaluación de tres dosis de potasio en la producción de lechuga (Lactuca sativa L. var. Crispa) bajo el sistema hidropónico recirculante NTF bajo invernadero - J. C., Manzano Ocaña; V. A., Lindao Córdova; A., Cabezas Huilca; J., Yánez Villacís; J. P., Cevallos Rodríguez; N. S., Erazo Sandoval; M., Leiva Mora (European Scientific Journal, ESJ, 2018)
Three doses of potassium were evaluated in the production of lettuce (Lactuca sativa L. var. Crispa), under the recirculable NFT hydroponic system in the greenhouse of the Department of Horticulture of the ESPOCH. A completely randomized block design was used with three treatments and three replications. The doses evaluated were: low dose (LD) with 224,33 ppm, medium dose (MD) with 470,00 ppm, and high dose (HD) with 716,67 ppm. Evaluated parameters were: potassium content in leaves and root, fresh weights of the aerial part and root, yield per net plot and hectare. The economic analysis was carried out according to the relation benefit/cost. The best results for most of the parameters evaluated were obtained with the low dose (LD), obtaining fresh weights of the aerial part and root of 193,01 and 36,65 g respectively. It has a yield per net plot of 2,04 kilograms and per hectare of 15338,75 kilograms, and the highest cost benefit with 4,63 dollars equivalent to 362,75%. On the other hand, the highest content of potassium in leaves and root up to 40 days after transplant (DAT) was obtained with the medium dose (MD) with 5,13 and 6,00% of total potassium, respectively. In all treatments, maintaining turgor in the plants throughout the cycle is very important. From the agronomic and economic point of view, the use a nutritive solution containing 224,33 ppm of potassium was recommended.